Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires